Sodium exclusion by different maize genotypes under salinity in conferring salt resistance - Khanoom, Mahrufa; Mojumder, Shawon; Uddin, Md Nesar; Ashrafuzzaman, Md; Fakir, Md Solaiman Ali (Asian Journal of Medical and Biological Research, 2017)
An experiment was carried out in the pot-house of botanical garden of Bangladesh Agricultural University (BAU), Mymensingh, during June to November, 2014 to investigate the effect of NaCl on growth, Na+ accumulation and K+: Na+ ratio in maize. Four maize genotypes namely BARI Maize 5, BARI Maize 7, Plain maize line and Mosaic maize line were tested against control, without providing any NaCl and salt stress, with NaCl to reach the soil salinity of 10 dS m-1. The experiment was laid out following CRD with four replicates. Under salt stress, relative reduction in shoot fresh masses were 22 and 77% in BARI Maize 5 and BARI Maize 7, whereas the magnitude of reduction was 136 and 155% in Mosaic maize line and Plain maize line, respectively. Seven days exposure to moderate salinity (10 dS m-1) seemed to have significantly reduced total fresh masses with the concomitant increase in Na+ concentrations but decrease in K+ concentrations and K+: Na+ ratios in both young and old shoots of BARI Maize 5, Plain maize line and Mosaic maize line. In contrast, BARI Maize 7 showed significant reduction in shoot fresh mass under salinity with the concomitant increase in shoot Na+ content but no significant changes in K+ concentrations and K+: Na+ ratios were observed under salinity. It seemed that young leaf of BARI maize 7 showed unaffected growth despite of higher accumulation of Na+. It may likely that BARI maize 7 sequestered incoming excess Na+ ions in the vacuole from the cytosol to combat deleterious effect of this ion to the cytoplasmic enzymes. Asian J. Med. Biol. Res. December 2016, 2(4): 562-566